Sources and consequences of oxidative damage from mitochondria and neurotransmitter signaling. (14th January 2016) - Brennan‐Minnella, Angela M.; Arron, Sarah T.; Chou, Kai‐ming; Cunningham, Eric; Cleaver, James E.
Abstract : Cancer and neurodegeneration represent the extreme responses of growing and terminally differentiated cells to cellular and genomic damage. The damage recognition mechanisms of nucleotide excision repair, epitomized by xeroderma pigmentosum (XP), and Cockayne syndrome (CS), lie at these extremes. Patients with mutations in the DDB2 and XPC damage recognition steps of global genome repair exhibit almost exclusively actinic skin cancer. Patients with mutations in the RNA pol II cofactors CSA and CSB, that regulate transcription coupled repair, exhibit developmental and neurological symptoms, but not cancer. The absence of skin cancer despite increased photosensitivity in CS implies that the DNA repair deficiency is not associated with increased ultraviolet (UV)‐induced mutagenesis, unlike DNA repair deficiency in XP that leads to high levels of UV‐induced mutagenesis. One attempt to explain the pathology of CS is to attribute genomic damage to endogenously generated reactive oxygen species (ROS). We show that inhibition of complex I of the mitochondria generates increased ROS, above an already elevated level in CSB cells, but without nuclear DNA damage. CSB, but not CSA, quenches ROS liberated from complex I by rotenone. Extracellular signaling by N‐methyl‐D‐aspartic acid in neurons, however, generates ROS enzymatically through oxidase that does lead to oxidative damage to nuclear DNA. The pathology of CS may therefore be caused by impaired oxidative phosphorylation or nuclear damage from neurotransmitters, but without damage‐specific mutagenesis. Environ. Mol. Mutagen. 57:322–330, 2016. © 2016 Wiley Periodicals, Inc.